Association of ethnicity and time to surgery among patients with chronic rhinosinusitis - Benjamin Tam; Casey Collet; Jessica Le; Ido Badash; Erick Garcia; Bozena Wrobel; Dale Rice; Kevin Hur (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objectives Determine factors associated with delayed endoscopic sinus surgery (ESS) in patients with chronic rhinosinusitis (CRS). Methods This is a retrospective cohort study conducted at a tertiary care academic center. Patients were included in the study if they were at least 18 years old and underwent surgery for CRS. Electronic medical records were retrospectively reviewed to collect demographic and clinical data. Patients with CRS secondary to another pathology such as malignancy were excluded. Multiple linear regression was performed to determine factors associated with the number of days between a patient's preoperative consultation and the date of surgery. Results A total of 103 patients with a mean age of 46.6 ± 16.8 years were included in the analysis; 51.5% of patients were females, 46.6% identified as White, and 29.1% identified as Hispanic. The majority of patients (67.0%) had preferred provider organization health insurance; 43.7% of patients had nasal polyps, 70.9% had a deviated nasal septum, and the mean preoperative Sinonasal Outcomes Test‐22 (SNOT‐22) score was 41.0 ± 23.8. The mean time to surgery after the final preoperative visit was 71.7 days ± 65.6 days. Hispanic ethnicity was associated with increased time to surgery (p < .05) when controlling for other variables. No other variables were associated with time to surgery on multivariate analysis. Conclusion Hispanic ethnicity may be an independent predictor of increased time to sinus surgery independent of disease severity and other demographic variables. Level of Evidence 2b